Laporan penemuan 1-kajian pelan pengurusan pembangunan persisir pantai Padang Mat Sirat-Ayer Hangat, Langkawi - Zainal, Megat Shahir; Che Hassan, Rozaimi; Mohd Saad, Nor Shah; Razak, Khamarrul Azahari; Abidin, Suriani; Asmawi, M. Zainora; Ujang, Kamaruzaman; Mohamad, Md Zahar; Mohamed, Mohd Zain (PLANMalaysia Pejabat Projek Zon Utara, 2020)
The Report of Findings (1) presents the results and analysis of all sectors involved in this study. Each chapter addresses their present condition, analysis of results and findings, and problems and issues of the study areas.